Fluorescent indicators for imaging membrane potential of organelles. (December 2022) - Klier, Pavel E.Z.; Roo, Ryan; Miller, Evan W.
Abstract: Plasma membrane potential is a key driver of the physiology of excitable cells like neurons and cardiomyocytes. Voltage-sensitive fluorescent indicators offer a powerful complement to traditional electrode-based approaches to measuring and monitoring membrane potential. Intracellular organelles can also generate membrane potential, yet the electrode- and fluorescent indicator-based approaches used for plasma membrane potential imaging are difficult to implement on intact organelles in their native environment. Here, we survey recent advances in developing and deploying voltage-sensitive fluorescent indicators to interrogate organelle membrane potential in intact cells.